The Pentingnya Game Wordwall dalam Pembelajaran untuk Meningkatkan Motivasi Belajar Peserta Didik melalui Tinjauan Literatur: Pentingnya Game Wordwall dalam Pembelajaran untuk Meningkatkan Motivasi Belajar Peserta Didik melalui Tinjauan Literatur - zedri; Selaras, Ganda Hijrah; Arsih, Fitri; Rahmi, Fitri Olvia (Al-Alam: Islamic Science Education Journal, 2025)
This study discusses the importance of motivation in the learning process, with a focus on the use of the educational game wordwall as a medium to enhance students’ learning motivation. The purpose of this study is to analyze the effectiveness of using wordwall in increasing students’ learning motivation based on a literature review. In the reviewed literature, the author found that low learning motivation is often caused by a lack of teacher innovation in utilizing technology. Using the Systematic Literature Review (SLR) method, this study collected and analyzed ten articles published between 2020 and 2025 that highlighted the effectiveness of wordwall. The analysis results indicate that wordwall not only enhances learning motivation but also improves students’ understanding of the material, critical thinking skills, and creativity. The gamification elements in wordwall create an interactive and enjoyable learning experience, effectively addressing the boredom often associated with conventional teaching methods. These findings emphasize the importance of integrating technology-based learning media into modern teaching strategies to improve the quality of education.